Untersuchungen zum Auftreten, zur Schadwirkung und zur Bekämpfung von Thysanopteren in Grassamenbeständen. - Wetzel, Theo (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The above publication deals with occurence, injury, and control of Thysanoptera in grass seeds of Alopecurus pratensis L., Phleum pratense L., Lolium perenne L., and Arrhenatherum elatius (L.) J. et С. Presl based upon the author's studies in the district of Lipsia during a period of four years. The grass Thysanoptera exhibit as to their life history an inhomogene group of pest insects. They mainly infest the flowers, where they induce empty spikes („Taubährigkeit") and cause considerable losses of seed. They do not cause total white spikes („Weißährigkeit"). The control of Thysanoptera in grass seeds is possible by means of agricultural or chemical measures.